East Asian renaissance: ideas for economic growth - "Gill, Indermit" (Washington D.C, 2007)
East Asia is a very different region today as compared with the early nineties, the place described in the book ""The East Asia Miracle"", previously published by the World Bank. China has emerged as the biggest development story during the nineties even as the region was wracked by the most severe economic crisis of the decade. While the rest of the world is trying to adjust, East Asia has already changed from a set of countries that rapidly integrated with the world to a region that is also aggressively exploiting the sources of dynamism that lie within Asia. The challenge now is to complement international with domestic integration. This book assesses the options for ensuring that East Asia's ""third integration"" is as potent as the first two.
Keywords: East Asia-Economic policy